Iteration for a Non-Self -Strongly Pseudocontractive Map - Ahmed, Buthainah; Hussian, Eman (Iraqi Journal of Science, 2023)
Let be a Banach space, be a nonempty closed convex subset of , and be selfnonexpansive map. The sequence generated by the iterative method, where be a contractive mappingand is a sequence in We generalize the mapping to non-sel -StronglyPseudocontractive .